Field-aligned currents in Saturn’s magnetosphere: Observations from the F-ring orbits - Hunt,GJ; Provan,G; Bunce,EJ; Cowley,SWH; Dougherty,MK; Southwood,DJ (Journal of Geophysical Research: Space Physics, 2018)
We investigate the azimuthal magnetic field signatures associated with highlatitude fieldaligned currents observed during Cassini's Fring orbits (October 2016–April 2017). The overall ionospheric meridional current profiles in the northern and southern hemispheres, that is, the regions poleward and equatorward of the fieldaligned currents, differ most from the 2008 observations. We discuss these differences in terms of the seasonal change between data sets and local time (LT) differences, as the 2008 data cover the nightside while the Fring data cover the postdawn and dusk sectors in the northern and southern hemispheres, respectively. The Fring fieldaligned currents typically have a similar four current sheet structure to those in 2008. We investigate the properties of the current sheets and show that the fieldaligned currents in a hemisphere are modulated by that hemisphere's “planetary period oscillation” (PPO) systems. We separate the PPOindependent and PPOrelated currents in both hemispheres using their opposite symmetry. The average PPOindependent currents peak at ~1.5 MA/rad just equatorward of the open closed field line boundary, similar to the 2008 observations. However, the PPOrelated currents in both hemispheres are reduced by ~50% to ~0.4 MA/rad. This may be evidence of reduced PPO amplitudes, similar to the previously observed weaker equatorial oscillations at similar dayside LTs. We do not detect the PPO current systems' interhemispheric component, likely a result of the weaker PPOrelated currents and their closure within the magnetosphere. We also do not detect previously proposed lower latitude discrete fieldaligned currents that act to “turn off” the PPOs.